Effect of Low-Dose Steroids as an Adjunct to Anti-Tubercular Therapy on Lymph Node Regression in Tuberculous Lymphadenitis: A Randomized Controlled Trial - Awan, Fahad Javed; Shahzed Ahmed Satti; Amna Butt; Muhammad Uneeb Ullah; Hafiz Asad Saeed; Farhan Zaid; Muhammad Hammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the effect of low-dose steroids in addition to anti-tubercular treatment on the regression of Lymph node size in patients with Tuberculous Lymphadenitis Study Design: Randomised Control Trial (NCT06236152). Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Sep 22 to Dec 23. Methodology: Patients with Tuberculous Lymphadenitis who presented to PEMH Rawalpindi were randomized into two groups of 55 patients each. Group-A was given low-dose steroids with ATT, and Group-B was given a placebo with ATT. Lymph node (LN) size was measured at start of treatment and followed up after 2 months and end of treatment. LN size regression was noted and compared in both groups along with incidence of side effects of steroids and ATT drugs. Results: The largest reported lymph node or the matted nodal mass size, before the start of the treatment was 4.09 ± 1.41 cm and 3.98 ± 1.26 cm in Group-A and Group-B respectively. In Group-A, 20 (36.4%) patients achieved regression in the lymph node size by 50% at the end of consolidation phase, whereas in Group-B 18 (32.7%) achieved the same (p=0.430). By the end of 6 months of treatment, 38 (69.1%) patients of Group-A had achieved regression in the lymph node size of more than 50% while 35 (63.6%) of the Group-B patients had achieved the same (p=0.235). Conclusion: A lower dose of prednisolone was of limited benefit and ineffective for regression of lymph node size as compared to alone standard ATT.